Analysis of driver's decision distance and merging distance in work zone area based on parametric survival models: With the aid of a driving simulator experiment. (May 2020) - Duan, Ke; Yan, Xuedong; Li, Xiaomeng; Hang, Junyu; Yang, Jingsi
Highlights: An in-depth analysis of lane changing in work zone is conducted through survival analysis. Survival models are established to explain relationship between influencing factors and lane changing. Work zone area is found to pose greater challenges for female drivers compared with male drivers. Lane-end sign shows limited effectiveness in guiding lane changing especially when placing far from work zone. Drivers under high traffic volume condition face greater risks due to aggressive driving behavior. Abstract: Work zones affect traffic safety and efficiency by changing the road condition and drivers' maneuver. Therefore, it is important to fully understand drivers' merging behavior in work zone related areas. In this study, a model framework composed of decision-distance analysis and merging-distance analysis was proposed, which could describe both decision-making and lane-changing process of merging behavior. A road environment with work zone was developed based on a driving simulator, and six scenarios composed of two levels of traffic volume and three different lane-end sign's locations were designed. Forty-two licensed participants, including 21 females (10 professional drivers vs. 11 normal drivers) and 21 males (15 professional drivers vs. 6 normal drivers) finally completed the experiment. Based on the experimental data, parametric survival models were established to analyze the effects of traffic sign location, traffic situation and driver characteristics on drivers' decision distance and merging distance. The results showed that: (i) the lane-end sign's location affected the decision point of lane changing and further affected the merging distance. However, the effect was weakened when the sign was placed far away from the work zone; (ii) merging distance in high traffic volume condition was shorter than that in low traffic volume condition; (iii) work zone posed greater challenges for female drivers as they merged later than males, and females were reluctant to adjust their merging distance according to different gap conditions. The findings shed some light on the future improvement of traffic design and management in work zones.